Aortic Root Diameter in Hypertensive Patients With Various Stages of Obstructive Sleep Apnea. (18th October 2021) - Wang, Dian; Xu, Jian-Zhong; Kang, Yuan-Yuan; Zhang, Wei; Hu, Lei-Xiao; Wang, Ji-Guang
Abstract: BACKGROUND: Obstructive sleep apnea (OSA) is a risk factor of several cardiovascular diseases. We investigated the association between aortic root diameter and hypoxia-related parameters in hypertensive patients with OSA. METHODS: Our study included 242 hypertensive patients with OSA (52 mild, 71 moderate, and 119 severe). All the patients underwent echocardiography for measuring aortic root diameter and polysomnography for measuring apnea–hypopnea index (AHI), oxygen desaturation index, and time spent with oxygen desaturation less than 90%. RESULTS: The study patients included 19.8% women and had a mean (±SD) age of 49.9 ± 12.9 years, a mean aortic root diameter of 33.4 ± 2.6 mm, and a prevalence of echocardiographic aortic root dilation of 3.7%. Patients with mild, moderate, and severe OSA had similar echocardiographic left ventricular structure. However, patients with severe OSA had a significantly ( P < 0.05) greater aortic root diameter (33.9 ± 2.4 mm vs. 32.4 ± 2.2 and 33.4 ± 2.9 mm, respectively) and higher prevalence of aortic root dilatation (5% vs. 1% and 3%, respectively) than those with mild and moderate OSA. Aortic root diameter corrected by body height was significantly ( P < 0.001) associated with AHI, oxygen desaturation index and time spent with oxygen desaturation less than 90% ( r = 0.23–0.33). After adjustment for various confounding factors, the associations between aortic root diameter and polysomnography parameters remained statistically significant ( P < 0.05). CONCLUSIONS: The severity of OSA was associated with the aortic root diameter. Patients with severe OSA had a greater aortic root diameter.